Aktivitas Askorbat Peroksidase dan Tanin pada Tanaman Karet (Hevea brasiliensis Muell. Arg.) Klon PB 260 dan RRIM 921 Kas Parsial dengan Pemberian Antidepresan - Bapoetra, Raihan Zaky; Rosmayati,; Kardhinata, E. Harso Kardhinata (Jurnal Online Pertanian Tropik, 2018)
The aim of the research was to determine the activity of ascorbic peroxide and tannin value on rubber plant clones PB 260 and RRIM 921 with partial Tapping Panel Dryness (TPD) which has been applied with a growth regulator. The results showed that RRIM 921 and PB 260 clones initiate significant value with productivity on 0 and 1 month observed also inactivity of ascorbic peroxide on 1 month observed. Plant condition with healthy and partial TPD showed significant value with tannin on 0 months observed. Positive correlation before the application was on APX and IP (0.060), APX and TSC (0.163), IP with productivity (0.154) and productivity with TSC (0.163). Positive correlation after the application was on APX and tannin (0.057), APX and TSC (0.051), tannin and IP (0.141), IP with productivity (0.316) and productivity with TSC (0.148.)